PENGGUNAAN MEDIA PEMBELAJARAN AUDIO VISUAL PADA MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM DI MI MA’ARIF NU 01 SOKAWERA KECAMATAN CILONGOK KABUPATEN BANYUMAS TAHUN PELAJARAN 2012/2013 - Umi Latifah (IAIN Purwokerto, 2018)
Abstract: This study aims to determine the use of audio-visual (movie) learning media on Islamic Culture History (SKI) subjects conducted in the first semester of class V MI Ma'arif NU 01 Sokawera Cilongok District, Banyumas Regency in the academic year 2012/2013. This research is field research using a qualitative descriptive approach. This research does not start from theory deduction, but starts from the field, namely empirical or inductive facts by studying a process or discovery that occurs naturally, recording, analyzing, interpreting, and reporting and drawing conclusions from the process. From the results of this study, the authors draw the conclusion that in the learning process there are several stages carried out by the teacher, namely: the delivery of material with the lecture model; giving reinforcement through audiovisual media (film screening); group discussion; group presentation; and giving questions. Keywords: Learning Media, Audio Visual, and Islamic Cultural History.